The fictional world of Javier Marías : language and uncertainty - Perez-Carbonell, Marta (Foro hispánico ;, 2016)
"The Fictional World of Javier Marías offers a fresh perspective on the narrative universe of one of Spain's most distinguished contemporary authors. In order to establish the origin and meaning of uncertainty in his fiction, this book presents interpretations of a range of issues inherent to Marías's canon, in particular those related to the nature of language. With the relationship between language and uncertainty at its heart, this study considers the use of foreign languages, translation, and the effect of silence through an analysis of: Todas las almas (1989), Corazón tan blanco (1992), Mañana en la batalla piensa en mí (1994) and Tu rostro mañana (2002-2007)"--